2017
DOI: 10.1021/jacs.7b09136
|View full text |Cite
|
Sign up to set email alerts
|

Remote Cooperative Group Strategy Enables Ligands for Accelerative Asymmetric Gold Catalysis

Abstract: An accelerative asymmetric gold catalysis is achieved for the first time via chiral ligand metal cooperation. An asymmetrically positioned remote amide group in the designed chiral binaphthyl-based ligand plays the essential role of a general base catalyst and selectively accelerates the cyclizations of 4-allen-1-ols into one prochiral allene face. The reactions are mostly highly enantioselective with achiral substrates, and due to the accelerated nature of the catalysis catalyst loadings as low as 100 ppm are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“…In 2017, Zhang, Zanoni, and co-workers chose to use the cyclization of allenols as a testing ground to validate a new chiral bifunctional ligand design for gold(I) catalysis ( Figure 65 a). 242 The researchers developed a ligand in which a basic amide is incorporated into the lower aryl ring of a chiral BINOL-derived phosphine scaffold ( Figure 65 b). It was proposed that in the transition state, the substrate orients itself such that the free alcohol is placed near to the amide carbonyl group, a good hydrogen bond acceptor, which can subsequently act as a general base and increase the nucleophilicity of the alcohol ( Figure 65 c).…”
Section: Carbon–heteroatom Bond-forming Reactionsmentioning
confidence: 99%
“…In 2017, Zhang, Zanoni, and co-workers chose to use the cyclization of allenols as a testing ground to validate a new chiral bifunctional ligand design for gold(I) catalysis ( Figure 65 a). 242 The researchers developed a ligand in which a basic amide is incorporated into the lower aryl ring of a chiral BINOL-derived phosphine scaffold ( Figure 65 b). It was proposed that in the transition state, the substrate orients itself such that the free alcohol is placed near to the amide carbonyl group, a good hydrogen bond acceptor, which can subsequently act as a general base and increase the nucleophilicity of the alcohol ( Figure 65 c).…”
Section: Carbon–heteroatom Bond-forming Reactionsmentioning
confidence: 99%
“…In addition, gold(I)-catalyzed addition reactions to unsaturated functional groups such as alkynes take place by outer sphere mechanisms, thus enhancing the degree of difficulty in developing enantioselective processes. Despite significant progress using axially chiral digold complexes, [43,115,116] phosphoramidite ligands, [117] the combination of non-chiral gold(I) complexes with chiral counterions [118] and other emerging strategies, [119][120][121][122][123][124] the asymmetric activation of alkynes which are not prochiral still presents an important challenge. In line with their pioneering studies, the group of Zhang reported bifunctional ligand L6 which enables the synthesis of chiral 2,5-dihydrofuranes 103 via enantioselective isomerization of propargylic alcohol 102 to axially chiral allenes followed by stereospecific cyclization (Scheme 19).…”
Section: Buchwald-type Ligands In Enantioselective Gold (I)-catalysismentioning
confidence: 99%
“…[121] Additionally, the same group reported a ligand-accelerated enantioselective cyclization of allenols. [122] Key to this transformation was the use of axially chiral ligand L7 with a remote amide group whereby hydrogen-bonding between ligand and substrate asymmetrically pre-orientates allenol 104 for nucleophilic attack giving vinyl tetrahydrofuranes 105.…”
Section: Buchwald-type Ligands In Enantioselective Gold (I)-catalysismentioning
confidence: 99%
“…Although the yield of the corresponding heterocycles 165 remained high, the enantioselectivity was low, no higher than 30% ee. The respective gold(I)-phosphine complexes were also used in the above-mentioned cyclization (Scheme 31) [113,114]. It should be underlined that axially chiral sterically hindered phosphines bearing amide function appeared to be excellent ligand for gold leading to the vinyl tetrahydrofurane derivatives 165 with high enantioselectivity [114].…”
Section: Furan Pyrrolidine and Indanone Derivativesmentioning
confidence: 99%